TEACHING READING TO THE STUDENTS: STRATEGIES AND SIGNIFICANCE (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores the importance of teaching reading, key approaches to instruction, and the role of educators in fostering literacy.